Revision of the butterfly genus Forsterinaria Gray, 1973 (Lepidoptera: Nymphalidae, Satyrinae) - Peña, Carlos (2005)
A taxonomic review of the Neotropical satyrine butterfly genus Forsterinaria Gray is presented herein, including a discussion of the classification and geographical distribution of its component species, illustrations of the adults of all taxa and the male genitalia of all species, and descriptions of 12 new species and two new subspecies: Forsterinaria antje sp. n., F. coipa sp. n., F. enjuerma sp. n., F. falcata sp. n., F. guaniloi sp. n., F. itatiaia sp. n., F. pallida sp. n., F. pallida aurita ssp. n., F. pichita sp. n., F. pilosa sp. n., F. punctata sp. n., F. pyrczi sp. n., F. rotunda sp. n., and F. rustica glendita ssp. n. Euptychia stelligera Butler, and E. fabiana Butler are sunk as synonyms (syn. n.) of Forsterinaria quantius (Godart). Euptychia magdalena Hayward, and E. pseudonecys Strand are sunk as synonyms (syn. n.) of F. inornata (C. Felder & R. Felder), and F. necys (Godart), respectively. Lectotypes are designated for 14 nominal taxa. A total of 23 species are recognized. A key for the identification of all taxa is presented.